Applied ergonomics of cycling performance - Kennedy, M. D.; Lampe, W. N. (Routledge handbook of ergonomics in sport and exercise, 2016)
Ergonomics `attempts to best understand the interaction among humans and other elements of a system in order to optimize human well-being and overall system performance` (International Ergonomics Association Council, 2000). As this concept relates to sport, ergonomics is a useful way of examining how athletes interact with their environment whereby a systematic process of athlete-environment assessment and training serves to enhance performance. This has been previously defined as the `mutual adjustment` of human and machine where the bicycle is the machine (de Groot et al., 1994), although a more current perspective on cycling ergonomics would include the interaction of the cyclist on his or her bicycle and the bicycle-rider unit in the surrounding environment (Debraux et al., 2011). Thus, this chapter will focus on the factors directly related to cycling velocity by exploring the relationship of the bicycle-rider unit with the external environment, and the factors that influence power output and are therefore indirectly related to cycling velocity by examining the bicycle-rider unit. This chapter will draw from road cycling and triathlon and focus on the three most typical cyclist positions: upright (hands on upper part or brake hoods of traditional road handlebar); drop (hands on bottom of traditional road handlebar); and time trial (elbows resting on pads on upper part of handler bar arms grasping `aerobar`)